Labour as a utility measure in contingent valuation studies: how good is it really? - Michael Ahlheim; Oliver Frör; Antonia Heinke; Nguyen Minh Duc; Pham Van Dinh (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2010)
The Contingent Valuation Method (CVM) aims at the assessment of people's willingness to pay (WTP) for a public project. The sum of the individual WTPs is interpreted as the social benefits of the project under consideration and compared to the project costs. If the benefits exceed the costs the project is recommended for realization. In very poor societies budgets are so tight that households cannot give up any part of their income, i.e. of their market consumption, in favour of a public project, so that their WTP for that project stated in a CVM interview has to be zero or close to zero. This leads to a severe discrimination against poor regions in the decision process on the allocation of public funds. Therefore, several authors suggest to use labour contributions to the realization of a public project instead of monetary contributions as a measure of people's WTP for that project. In this paper we show theoretically and empirically, based on a CVM study conducted in Vietnam, that labour is severely flawed as a measuring rod for individual utility so that CVM based on labour contributions does not provide a reliable and meaningful decision rule for the allocation of public projects.
urn:nbn:de:bsz:100-opus-4332
Keywords: D6; H4; L3; Q25; Q51; 330; Cost-benefit analysis; Contingent Valuation; developing countries; public expenditures; Kosten-Nutzen-Analyse; Willingness to pay; Arbeit; Entwicklungsländer; Vietnam